(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
Metaphorsarewidelyusedinthepresstodayasoneofthelexicalandstylistictools, theirimportanceisespeciallyinattractingtheaudience and accelerating the acquisition of new ideas and new concepts. Their use is closely related to the structural structure of the newspaper text and its approach to spiritual or economic phenomena. This article analyzes the importance of identifying the linguostylistic functions of metaphors in newspaper texts, understanding their position and impact in social, political or economic reality.